2022
DOI: 10.1111/nph.18111
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA172 controls inflorescence meristem size through regulation of APETALA2 in Arabidopsis

Abstract: The APETALA2 (AP2) transcription factor regulates flower development, floral transition and shoot apical meristem (SAM) maintenance in Arabidopsis. AP2 is also regulated at the post-transcriptional level by microRNA172 (miR172), but the contribution of this to SAM maintenance is poorly understood.We generated transgenic plants carrying a form of AP2 that is resistant to miR172 (rAP2) or carrying a wild-type AP2 susceptible to miR172. Phenotypic and genetic analyses were performed on these lines and mir172 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…AP2-type PmuVar_Ch1_1236 is also on chromosome 1, but studies in Arabidopsis indicate that expression of miR172-resistant versions of either AP2 or TOE3 (AP2-type euAP2 transcription factors) under their native promoters resulted in enlarged floral meristems and the production of supernumerary stamens, whereas supernumerary petals and an indeterminate floral meristem were obtained only when a constitutive promoter was used 17 , 26 , 27 , suggesting they have no direct role in determining floral patterning, but their miss-expression could perturb the activity of TOE-type euAP2 genes during flower development. This was substantiated in a recent study 28 which also confirmed previous reports that miR172-mediated regulation of these genes occurs through the modulation of protein translation rather than post-transcriptional mRNA degradation 26 , 29 , 30 . As compared to the counterpart from a wild P. mume genome and the sequences from closely related species P. persica and P. armenica (Supplementary File 1 ), the pmTOE sequence from the genome of DF cultivar tortuosa , pmTOE DEL , revealed a 49 bp deletion affecting the miR172d target site, similar to those found to be sufficient to give the phenotype when found in PET genes from peach, roses and dianthus, or induced in tobacco 11 14 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…AP2-type PmuVar_Ch1_1236 is also on chromosome 1, but studies in Arabidopsis indicate that expression of miR172-resistant versions of either AP2 or TOE3 (AP2-type euAP2 transcription factors) under their native promoters resulted in enlarged floral meristems and the production of supernumerary stamens, whereas supernumerary petals and an indeterminate floral meristem were obtained only when a constitutive promoter was used 17 , 26 , 27 , suggesting they have no direct role in determining floral patterning, but their miss-expression could perturb the activity of TOE-type euAP2 genes during flower development. This was substantiated in a recent study 28 which also confirmed previous reports that miR172-mediated regulation of these genes occurs through the modulation of protein translation rather than post-transcriptional mRNA degradation 26 , 29 , 30 . As compared to the counterpart from a wild P. mume genome and the sequences from closely related species P. persica and P. armenica (Supplementary File 1 ), the pmTOE sequence from the genome of DF cultivar tortuosa , pmTOE DEL , revealed a 49 bp deletion affecting the miR172d target site, similar to those found to be sufficient to give the phenotype when found in PET genes from peach, roses and dianthus, or induced in tobacco 11 14 .…”
Section: Discussionsupporting
confidence: 87%
“…The effects of single nucleotide mutations altering the miR172 binding site of PETALOSA gene orthologs have already been shown to induce extra-numerary petals in gene-edited tobacco plants 13 and it is therefore plausible that pmPET SNP1 and pmPET SNP2 represent alternative alleles leading to flower doubleness in the mei germplasm, alongside pmTOE DEL that we found more commonly associated with the trait. These kind of mutations are known to work at the mRNA level 26 , 28 30 , however as a result of translation, pmTOE DEL and pmPET SNP1 would also result in a deletion and/or frame-shift of the N-ter end of the translated peptides, while pmPET SNP2 is predicted to result in a missense mutation directly causing a truncated protein product, although all functional euAP2 domains are predicted to be retained (Supplementary File 1 C). pmTOE DEL allele, either homozygous or heterozygous is well distributed across the various phylogenetic clusters, while pmPET SNP2 allele is shared by only five subgroups (including individuals sampled in France, Japan and different regions of China).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with the negative role played by auxin in SAM enlargement (Zhao et al, 2010; Shi et al, 2018; Zhang et al, 2018; Ma et al, 2019). Aside from auxin levels, ARF3 was reported to maintain SAM size by repressing the expression of APETALA2 ( AP2 ) in the Arabidopsis SAM (Sang et al, 2022). The loss‐of‐function arf3 mutant produces an enlarged SAM (Sang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from auxin levels, ARF3 was reported to maintain SAM size by repressing the expression of APETALA2 ( AP2 ) in the Arabidopsis SAM (Sang et al, 2022). The loss‐of‐function arf3 mutant produces an enlarged SAM (Sang et al, 2022). Further supporting the negative role of auxin in SAM enlargement and multi‐locule formation of SlTPL3‐ RNAi plants, RNA‐seq profiling revealed that SlIAA17 , encoding a repressor of auxin signaling, and SAUR are downregulated in SlTPL3‐ RNAi lines, whereas SlYUCCA8 (auxin biosynthesis) and SlPIN3 (auxin transport) were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory module of miR172- AP2 has been highlighted in regulating fruit development in diverse plants. In Arabidopsis , miR172 promotes the silique fruit expansion process by the negative regulation of the activity of the APETALA2-like ( AP2 ) gene [ 19 ], which would otherwise hinder the action of AGAMOUS ( AG ) and FRUITFUL ( FUL ) [ 20 ], two MADS-box transcription factors that are essential for ovary and silique growth [ 21 ]. miR172 has an adverse influence on fruit size in apples ( Malus × domestica ) through the negative regulation of AP2 that is required for hypanthium development into a pome fruit [ 22 ], resulting in small fruit size and an abnormal floral organ [ 23 ].…”
Section: Functions Of Mirnas and Lncrnas In Fruit Developmentmentioning
confidence: 99%